New diagnoses of human immunodeficiency virus infection in the Spanish pediatric HIV Cohort (CoRISpe) from 2004 to 2013. Issue 39 (September 2017) - Jiménez de Ory, Santiago; González-Tomé, María Isabel; Fortuny, Claudia; Mellado, Maria Jose; Soler-Palacin, Pere; Bustillo, Matilde; Ramos, José Tomas; Muñoz-Fernández, Maria Angeles; Navarro, Maria Luisa
Abstract : Abstract: Vertical human immunodeficiency virus (HIV) infection has decreased in industrialized countries in recent decades, but there are no studies on the mechanisms of HIV transmission among infected children in Spain. Our aim was to study the characteristics and trends of diagnoses of vertically HIV-infected children in Spain from 2004 to 2013. Vertically HIV-infected children were selected if they were diagnosed from 2004 to 2013, were aged 0 to 18 years old, and were included in the Cohort of the Spanish Pediatric HIV Network (CoRISpe). Demographic, clinical, immunological, and virological data at diagnosis were obtained. The rate of diagnoses of vertically HIV-infected children was calculated as the number of cases per 100, 000 inhabitants. Obstetric data of mothers of Spanish children and prophylaxis at childbirth and postpartum were obtained. A total of 218 HIV-infected children were included in the study. Of this sample, 182 children (83.5%) were perinatally HIV infected, and 125 out of those 182 children (68.7%) were born in Spain. The vertically HIV-infected Spanish children were diagnosed earlier and were in better clinical and immunological condition at diagnosis than were foreign children. The rate of vertically HIV-infected children declined from 0.09 in 2004 to 0.03 in 2013 due to the decrease in the rate of children born in Spain (0.08 in 2004 vs 0.01 in 2013). A total of 60 out of 107 mothers (56.1%) of Spanish children were diagnosed at or after childbirth. However, this number declined between 2004 and 2013. The rate of new HIV diagnoses of vertically HIV-infected children decreased significantly between 2004 and 2013 from 0.09 to 0.03 per 100, 000 inhabitants.